2022
DOI: 10.3390/pediatric14040060
|View full text |Cite
|
Sign up to set email alerts
|

The Association between SARS-CoV-2 Infection and Diabetic Ketoacidosis in Patients with New-Onset Diabetes: A Retrospective Study from a Diabetic Center in Saudi Arabia

Abstract: Background: Various reports described new-onset diabetes during or after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with no previous history of diabetes or glucocorticoid use. Further, SARS-CoV-2 could increase the risk of diabetes, including diabetic ketoacidosis (DKA). However, data on the relationship between new-onset diabetes and COVID-19 are still limited in our region. Thus, we aimed in this study to evaluate the association between new-onset diabetes and DKA in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…SARS‐CoV‐2 infection was defined by first positive PCR test for SARS‐CoV‐2 in all included studies. The control group in six studies was from non‐COVID‐19 participant 2–4,6–8 and in one study selected from patients with other respiratory tract infections 5 . Studies reported the risk of new‐onset T1DM based on adjustment for age, 3,8 gender, 3,7,8 geographical area and socioeconomic factors, comorbidity, vaccine doses, parental history of T1DM, 7 and calendar time 6,7 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SARS‐CoV‐2 infection was defined by first positive PCR test for SARS‐CoV‐2 in all included studies. The control group in six studies was from non‐COVID‐19 participant 2–4,6–8 and in one study selected from patients with other respiratory tract infections 5 . Studies reported the risk of new‐onset T1DM based on adjustment for age, 3,8 gender, 3,7,8 geographical area and socioeconomic factors, comorbidity, vaccine doses, parental history of T1DM, 7 and calendar time 6,7 .…”
Section: Resultsmentioning
confidence: 99%
“…All meta-analyses in the current study were conducted using Review Manager (version 5.4; The Nordic Cochrane Center) and a two-sided p value less than 0.05 was considered statistically significant. was from non-COVID-19 participant [2][3][4][6][7][8] and in one study selected from patients with other respiratory tract infections. 5 Studies reported the risk of new-onset T1DM based on adjustment for age, 3,8 gender, 3,7,8 geographical area and socioeconomic factors, comorbidity, vaccine doses, parental history of T1DM, 7 and calendar time.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we studied alcohol and substance abuse, which was not previously studied in Saudi Arabia [ 13 ], and our sample was homogeneous, increasing the accuracy of our results. We recommend further longitudinal, prospective clinical studies with an extensive and representative sample to understand the association between ACEs and T2DM [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%